Participatory Action Research in Afro-Latin America : a methodology to imagine and build a life in dignity - Gruber, Valerie (ECAS9 2023: 9th European Conference on African Studies "African Futures", 2023)
Participatory approaches to knowledge production address an urgent need in African and African Diaspora studies: they are laboratories to imagine and develop research practices targeted at overcoming social, racial and gendered hierarchies. Based on two years of doing Participatory Action Research (PAR) with Afro-descendant communities from Brazil and Colombia, we will present diverse methods of knowledge co-creation carried out both online and on-site. Thereby, artistic forms of expression such as music, dance and poetry are used as a common language to imagine life in dignity and identify strategies to achieve this vision. Accompanied by an online mentoring process, our PAR group produced several video performances during the pandemic and published them on the DjumbaiALA YouTube channel (https://www.youtube.com/@djumbaiala). In 2022, we realized the actual exchange program in Cartagena (Colombia) and Salvador da Bahia (Brazil), bringing together young artists and community actors from both countries. We found that the imagination of alternative futures is only possible if hierarchies in formal education, gender, race or class do not inhibit an open exchange of ideas and concepts. This requires a high level of empathy and constant dialogue, taking advantage of methodologies stemming from social arts and arts education. Reflecting on these experiences sheds light on diverse possibilities to co-create academic and artistic knowledges as well as the potentials and limitations of transdisciplinary online and on-site collaboration. This aims at inspiring researchers and professionals who intend to ground their work with Black communities on reciprocity and mutual learning, while boosting creativity, equality and decoloniality.
Keywords: knowledge co-creation; Afro-descendant artists; methodology; mutual benefit